Design and Build Vocational Choice Applications in Vocational Schools Using the SAW (Simple Additive Weighting) Method - Ardiyanti, Sri; Anwar, Muhammad; Hendriyani, Yeka; Waskito (AI Society & STMIK Indonesia, 2023)
Vocational High Schools provide knowledge of skills, interests, and talents according to vocational fields to face the world of work. The phenomenon that occurred in February 2022 stated that most SMK graduates were ready to work. Because of this, the data from the Central Bureau of Statistics on SMK graduates have a total score of 10.38%. So there is unemployment and a lack of interest and talent in choosing a vocational field. Based on information in determining vocational fields based on interests, talents, and colleagues there is no discrepancy between the major one chooses and personality. In measuring products, the Simple Additive Weighting method can be used to select the best alternative in the ranking process which totals the weight values ​​of all criteria.